Empowering teachers: a growth mindset program for enhanced facilitating learning in primary schools - Khunaprom, Tantikorn; Chansirisira, Pacharawit (Journal of Education and Learning (EduLearn), 2025)
Teachers who adopt a growth mindset significantly enhance student development, facilitating learning, and continuous improvement, leading to better student learning outcomes and a more positive learning environment. This research aimed to develop a growth mindset to improve the facilitating learning skills of primary school teachers. The research utilized a development (RD) method, structured into four phases: i) analyzing components and indicators; ii) assessing needs; iii) developing the program; and iv) implementing the program. The study focused on creating training to influence teachers’ mindsets and drive changes in practice. A mixed methods design was used, with the growth mindset development program consisting of 6 modules over 120 hours. This program incorporated training or self-learning, learning through collaboration, and integrating operational practices, involving 15 volunteer teachers. Results indicated a statistically significant shift in mindset between pre-and post-intervention measures, which was sustained after three months. The program fostered a professional learning community focused on developing a growth mindset, refining teaching techniques, and enhancing student learning outcomes. Overall, the growth mindset program proved highly effective for primary school teachers, greatly expanding their knowledge and cultivating a professional learning community that positively impacts student development and facilitating learning skills of teachers.